Redesign of User Experience in Inaportnet Using the User Experience Questionnaire Method TND User-Centered Design - muhamad irvandra irvan; muhamad Jazman jazman; Eki Saputra Eki; Syaifullah; Tengku Khairil Ahsyar (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The Directorate General of Sea Transportation, under Indonesia's Ministry of Transportation, developed Inaportnet as a digital platform mandated by Ministerial Regulation Number PM 8 of 2022 to streamline ship service procedures and enhance e-government implementation. This study evaluates the user experience (UX) of the Inaportnet website, focusing on its usability, security, and overall design using a user-centred design (UCD) approach and the User Experience Questionnaire (UEQ) method. Data were collected from 56 respondents, including stakeholders such as ship operators, port authorities, and service users. The findings reveal critical shortcomings: 95% of respondents encountered frequent bugs affecting usability, 65% highlighted security concerns, 60% criticised the cluttered interface, 40% experienced access failures, and 50% expressed low engagement with the platform's features. To address these challenges, the website was redesigned using UCD principles, resulting in significant improvements. The redesigned platform achieved "Good" ratings for attractiveness, stimulation, and novelty, and "Above Average" ratings for clarity, efficiency, and accuracy in UEQ metrics, indicating enhanced usability and user satisfaction. This study underscores the importance of iterative UX design in optimising digital government systems, offering actionable insights for improving public service platforms in developing countries.